Generative artificial intelligence tools in journal article preparation: A preliminary catalog of ethical considerations, opportunities, and pitfalls* - Robin R. White (JDS Communications)
The launch of generative artificial intelligence (GenAI) tools has catalyzed considerable discussion about the potential impacts of these systems within the scientific article preparation process. This symposium paper seeks to summarize current recommendations on the use of GenAI tools in scientific article preparation, and to provide speculations about the future challenges and opportunities of GenAI use in scientific publishing. Due to the dynamic nature of these tools and the rapid advancement of their sophistication, the most important recommendation is that ongoing engagement and discussion within the scientific community about these issues is critical. When using GenAI tools in scientific article preparation, humans are ultimately accountable and responsible for products produced. Given that accountability, an expert panel convened by the National Academies of Science, Engineering, and Medicine recently proposed principles of GenAI use in science communication, including (1) transparent disclosure and attribution; (2) verification of AI-generated content and analyses; (3) documentation of artificial intelligence (AI)-generated data; (4) a focus on ethics and equity; and (5) continuous monitoring, oversight, and public engagement. In addition to the importance of human accountability, many publishers have established consistent policies suggesting that GenAI tools should not be used for peer reviewing, figure generation or manipulation, or assigned authorship on scientific articles. Along with the potential ethical challenges associated with GenAI use in scientific publishing, there are numerous potential benefits. Herein we summarize example conversations demonstrating the capacity of GenAI tools to support the article preparation process, and an example standard operating procedure for human-AI interaction in article preparation. Finally, diverse broader questions about the impact of GenAI tools on communication, knowledge, and advancement of science are raised for rumination.